Penghapusan Kekerasan dalam Rumah Tangga Prespektif Al-Qur’an - Alinurdin, M.; Abubakar, Achmad; Parhani, Aan (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Domestic violence is one of the national and even international problems that have not yet been dealt with until now. Based on reports from related institutions, in Indonesia, cases of domestic violence, especially against women, continue to increase from year to year. Many studies and views have emerged about the causes of the increase in violence. Some views consider that one of the causes of violence is because of religious legitimacy in which there are verses of the Qur'an that support violence against women. This study examines the content of the meaning of the verse and the argument of the compatibility of Islam with the movement to eliminate domestic violence. Regarding to the focus of the study, the research found: First, the interpretation of the word 'wad}ribu>hunna' in al-Nisa/4:34 is not interpreted as an order to beat a wife if she disobeys but is just a permissibility. Nor is it allowed to hit absolutely but is limited by strict conditions. Second, there are many arguments from the Qur'an that support the elimination of various forms of domestic violence which are reinforced by the hadith of the Prophet Muhammad. This proves that Islam is in line with the legislation on the elimination of domestic violence at national and international levels.